MANAJEMEN PEMANTAUAN KUALITAS AIR DI LINGKUNGAN PT. BUMI SUKSESINDO, BANYUWANGI, JAWA TIMUR - Annisatun Nadzafah; Maitsa Fikri Nabila; Pramudya Bagas Utama (Hexagon, 2025)
One of the main challenges in mining activities is environmental issues, especially the risk of damage to natural resources. In general, mining activities aim to maximize the utilization of mining resources that exist on the earth. PT Bumi Suksesindo (PT BSI), as the first national private company in Java Island engaged in high sulfidation epithermal gold mining, strives to implement good environmental management and monitoring practices in every stage of its mining activities, from exploration to production, by applicable regulations. This study aims to review the water quality at PT Bumi Suksesindo, Banyuwangi, East Java. It is found that PT Bumi Suksesindo carries out water quality monitoring consistently and refers to the regulation, namely the Regional Regulation of East Java Province Number 2 of 2008 concerning Water Quality Management and Water Pollution Control in East Java Province.